One-step silane crosslinking type halogen-free flame-retardant material as well as preparation method and application thereof
Through the improved preparation method of silane crosslinked halogen-free flame retardant material, the problems of poor extrusion surface quality and high time and energy consumption during the one-step preparation process of silane crosslinked polyethylene in the prior art are solved, and high efficiency and low energy are achieved It consumes production process and is suitable for cable routing in tight spaces.
Patent Information
- Application Number
- CN202411756186.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-14
AI Technical Summary
During the one-step preparation process of existing silane crosslinked polyethylene, it is easy to lead to poor extrusion surface quality and long time and energy consumption, affecting production efficiency and cost.
Using an improved preparation method of silane crosslinked halogen-free flame retardant material, the speed and uniformity of silane adsorption are improved by granulating most of the powdered SEBS with other raw materials and mixing them with the remaining SEBS and silane. , reduce process steps such as heating and vacuuming.
It improves the extruded surface quality, shortens production time and energy consumption, improves production efficiency, reduces production costs, and is suitable for occasions with small wiring space.
Smart Images

Figure BDA0005168597170000111 
Figure BDA0005168597170000112
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, in particular to insulating materials for cables, and specifically to a one-step silane cross-linking halogen-free flame retardant material and a preparation method and application thereof. Background Art
[0002] Generally, thermoplastic elastomer materials are prone to plastic deformation in high temperature situations and are only suitable for use in situations where heat resistance requirements are not high. Thermoplastic elastomer materials are not suitable for situations where the instantaneous temperature is high and the elastomer is prone to deformation and failure. The commonly used method at present is to use cross-linking to improve the heat resistance of the material. For example, silane cross-linked polyethylene is commonly used, but its hardness is generally around 97A or 50D. For conventional cable applications, because the wiring space is large, the hardness has no obvious effect on the wiring. However, for situations such as automobiles and electrical equipment where the wiring space is small, excessive cable hardness will seriously affect the wiring.
[0003] At the same time, silane cross-linked polyethylene is generally prepared by two methods: the first is a one-step method, and the process generally includes heating the drying silo, drying the base material, heating the shake tank, vacuuming the shake tank, inhaling silane and nitrogen, and adsorbing silane, so as to obtain a masterbatch in which silane is mixed in the material body without grafting, and then mixed with other materials in the cable factory for silane grafting and synchronous extrusion of cables, and then cross-linking; the second is a two-step method, that is, first grafting silane onto the resin material body in the extruder to obtain a grafted material body, and then mixing it with other materials in the cable factory for cable extrusion, and then cross-linking; the two methods have their own advantages and disadvantages.
[0004] The hardness of SEBS elastomer can be adjusted in a wide range. If it is used as an auxiliary material or main material, it can be beneficial to obtain cable materials with relatively lower hardness. However, it is found in practice that if the silane cross-linked polyethylene is prepared by a one-step method, silane cross-linked SEBS-based elastomer material will contain more pores in the extruded insulation or sheath layer, resulting in poor extrusion surface quality. In severe cases, it may even affect the performance of the cable and make it unusable. On the other hand, the whole process takes a long time, and many equipment devices need to be heated, which is time-consuming and energy-consuming, and is not conducive to reducing production costs. Summary of the invention
[0005] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved one-step method for producing a silane cross-linked halogen-free flame retardant material, wherein the material produced by the method is improved at least in terms of extrusion surface quality, time consumption and energy consumption.
[0006] The present invention also provides a silane cross-linked halogen-free flame retardant material prepared by the above method and its application in preparing insulating materials for electronic wires, new energy vehicle charging pile cables and in-vehicle connecting cables.
[0007] In order to achieve the above object, a technical solution adopted by the present invention is:
[0008] A method for preparing a silane cross-linked halogen-free flame retardant material, the preparation method comprising:
[0009] (1) Preparation of silane masterbatch
[0010] The first linear low-density polyethylene, the first antioxidant, 90 wt.% to 99.9 wt.% of the first SEBS and the processing base oil are uniformly mixed, and then the flame retardant is added, and after the mixture is uniformly mixed, the mixture is banburyed and extruded into granules, and the obtained particles, the remaining 0.1 wt.% to 10 wt.% of the first SEBS and the silane dissolved with the initiator are mixed to obtain a silane masterbatch without silane grafting;
[0011] Wherein, in parts by weight, the silane masterbatch comprises 40 to 60 parts of the first SEBS, 40 to 60 parts of the first linear low-density polyethylene, 2.0 to 6.0 parts of silane, 0.04 to 0.3 parts of initiator, 25 to 35 parts of processing base oil, 75 to 125 parts of flame retardant, and 1.0 to 6.0 parts of the first antioxidant; the silane is vinyl triethoxysilane;
[0012] (2) Preparation of catalytic masterbatch
[0013] The second linear low-density polyethylene, the second SEBS, the catalyst and the second antioxidant are mixed, kneaded, extruded and granulated to obtain a catalyst masterbatch;
[0014] Wherein, in the catalyst masterbatch, by weight, the second linear low-density polyethylene is 90 to 99.5 parts, the second SEBS is 0.5 to 10 parts, the catalyst is 0.5 to 3 parts, and the second antioxidant is 0.5 to 4 parts;
[0015] The molecular weights of the first SEBS and the second SEBS are respectively 80,000 to 230,000.
[0016] In some embodiments of the present invention, during the preparation of the silane masterbatch, 95 wt.% to 99.9 wt.% of the first SEBS is added before the banburying.
[0017] Furthermore, in the preparation process of the silane masterbatch, 97 wt.% to 99.5 wt.% of the first SEBS is added before the banburying.
[0018] In some embodiments of the present invention, during the preparation of the silane masterbatch, the temperature of the obtained particles is controlled to be less than or equal to 50° C. before mixing with other materials.
[0019] In some embodiments of the present invention, during the preparation of the silane masterbatch or the catalytic masterbatch, the temperature of the banburying is 140-160°C.
[0020] In some embodiments of the present invention, during the preparation of the silane masterbatch or the catalytic masterbatch, the extrusion granulation is performed using a twin-screw extruder and a single-screw extruder in sequence.
[0021] Further, the temperature of each section of the twin-screw extruder is as follows: zone 1 120-130°C, zone 2 125-135°C, zone 3 130-140°C, zone 4 135-145°C, zone 5 140-150°C, zone 6 145-155°C, zone 7 150-160°C, zone 8 150-160°C, zone 9 150-160°C, and die head temperature 150-160°C;
[0022] The temperature of each section of the single-screw extruder is as follows: zone 1 130-140°C, zone 2 135-145°C, zone 3 140-150°C, and die head temperature 145-155°C.
[0023] In some embodiments of the present invention, in the silane masterbatch, the total amount of the first SEBS and the first linear low-density polyethylene is 100 parts.
[0024] In some embodiments of the present invention, in the catalytic masterbatch, the total amount of the second linear low-density polyethylene and the second SEBS is 100 parts.
[0025] In some embodiments of the present invention, the silane masterbatch further comprises a lubricant. In parts by weight, the lubricant accounts for 1.5 to 2.5 parts of the silane masterbatch.
[0026] Furthermore, the lubricant is a PE-based silicone masterbatch, and the silicone content is 40wt.% to 60wt.%.
[0027] In some embodiments of the present invention, in the silane masterbatch or the catalyst masterbatch, the first antioxidant and the second antioxidant are the same.
[0028] Furthermore, the first antioxidant and the second antioxidant are respectively composed of antioxidant 1010, antioxidant 300, and antioxidant 1024 in a ratio of 1:0.8-1.2:0.8-1.2.
[0029] In some embodiments of the present invention, at a temperature of 190° C. and a load of 2.16 kg, melt mass flow rates of the first linear low-density polyethylene and the second linear low-density polyethylene are respectively 1 to 3 g / 10 min.
[0030] In some embodiments of the present invention, the flash point of the processing base oil is above 260° C. The processing base oil may be naphthenic oil.
[0031] In some embodiments of the present invention, the initiator is dicumyl peroxide.
[0032] In some embodiments of the present invention, the flame retardant is magnesium hydroxide and / or zinc borate.
[0033] In some embodiments of the present invention, the catalyst is dibutyltin dilaurate.
[0034] In some embodiments of the present invention, the feed mass ratio of the silane masterbatch to the catalyst masterbatch is 90-99:10-1.
[0035] Another technical solution provided by the present invention is a silane cross-linked halogen-free flame retardant material prepared by the preparation method of the silane cross-linked halogen-free flame retardant material described above.
[0036] Another technical solution provided by the present invention is: a silane cross-linked halogen-free flame retardant material, wherein the silane cross-linked halogen-free flame retardant material comprises a silane masterbatch and a catalytic masterbatch;
[0037] In parts by weight, the silane masterbatch comprises 40 to 60 parts of the first SEBS, 40 to 60 parts of the first linear low-density polyethylene, 2.0 to 6.0 parts of the silane, 0.04 to 0.3 parts of the initiator, 25 to 35 parts of the processing base oil, 75 to 125 parts of the flame retardant, and 1.0 to 6.0 parts of the first antioxidant; the silane is vinyl triethoxysilane;
[0038] In terms of weight, the catalytic masterbatch comprises 90 to 99.5 parts of the second linear low-density polyethylene, 0.5 to 10 parts of the second SEBS, 0.5 to 3 parts of the catalyst, and 0.5 to 4 parts of the second antioxidant;
[0039] The molecular weights of the first SEBS and the second SEBS are respectively 80,000 to 230,000.
[0040] Furthermore, the molecular weights of the first SEBS and the second SEBS are respectively 80,000 to 180,000.
[0041] Another technical solution provided by the present invention is: an application of the above-mentioned silane cross-linked halogen-free flame retardant material in the preparation of insulating materials for electronic wires, new energy vehicle charging pile cables and in-vehicle connecting cables.
[0042] In the present invention, "first" and "second" are only used to describe and distinguish the raw materials used in different material bodies, and there is no order relationship.
[0043] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0044] The present invention provides an improved silane cross-linked halogen-free flame retardant material and an improved preparation process thereof. The silane cross-linked halogen-free flame retardant material can not only be produced by a one-step method, but also has high extrusion surface quality. The entire process is short in time and low in energy consumption, which greatly improves production efficiency and reduces production costs, and is conducive to large-scale industrial production. Moreover, the cable material made of the silane cross-linked halogen-free flame retardant material has excellent mechanical properties and suitable hardness, and can be used in occasions where wiring space is narrow. DETAILED DESCRIPTION
[0045] In practice, the inventors of the present invention introduced SEBS elastomer in order to adjust the hardness of the cable material. However, the following problems occurred when preparing silane-crosslinked SEBS-based elastomer material by a one-step method of silane-crosslinked polyethylene: on the one hand, the extruded insulation or sheath layer contains more pores, resulting in poor extrusion surface quality, and even affecting the performance of the cable and making it unusable in severe cases; on the other hand, the whole process takes a long time, and multiple equipment devices need to be heated, which is time-consuming and energy-consuming, and is not conducive to reducing production costs;
[0046] After a large number of experimental studies, it is believed that the reason is that the introduced SEBS elastomer is a powdery raw material, and the flame retardant itself is also in powder form. Such a large amount of powder causes a large amount of gas to be mixed between the loose powders during one-step production and is brought into the single-screw extruder used for cable production. It is difficult for the single-screw extruder to completely remove a large amount of gas during the extrusion process in a short time, resulting in more pores in the extruded insulation or sheath layer. Based on this, the present invention innovatively provides an improved silane cross-linked halogen-free flame retardant material and an improved preparation process thereof. The present invention innovatively adopts two materials, one is a silane masterbatch without silane grafting, and the other is a catalytic masterbatch containing a catalyst, and the raw materials of the two masterbatches are The materials are matched and the content is set, especially in the preparation process of the silane masterbatch, most of the powdered first SEBS is creatively granulated with other raw materials including flame retardants, and then mixed with the remaining powdered first SEBS ethyl silane containing an initiator. This not only greatly improves the speed and uniformity of silane adsorption, but also surprisingly finds that the material heating, vacuuming, nitrogen filling and other processes in the one-step silane cross-linking polyethylene process can be omitted. While achieving excellent results, the energy consumption and time consumption are greatly reduced, which has significant advantages for large-scale industrial production. In addition, the product of the present invention can adopt a natural cross-linking method, which saves energy and water compared with hot water or steam cross-linking, and does not require related equipment investment.
[0047] The present invention is further described below in conjunction with the specific formula and preparation process.
[0048] The silane cross-linked halogen-free flame retardant material comprises a silane masterbatch and a catalytic masterbatch; in parts by weight, the silane masterbatch comprises 40 to 60 parts of a first SEBS, 40 to 60 parts of a first linear low-density polyethylene, 2.0 to 6.0 parts of a silane, 0.04 to 0.3 parts of an initiator, 25 to 35 parts of a processing base oil, 75 to 125 parts of a flame retardant, and 1.0 to 6.0 parts of a first antioxidant; the silane is vinyl triethoxysilane; in parts by weight, the catalytic masterbatch comprises 90 to 99.5 parts of a second linear low-density polyethylene, 0.5 to 10 parts of a second SEBS, 0.5 to 3 parts of a catalyst, and 0.5 to 4 parts of a second antioxidant.
[0049] In some cases, the molecular weights of the first SEBS and the second SEBS are respectively 80,000 to 230,000, which can improve the processing performance in the system of the present invention, for example, 80,000 to 120,000, 120,000 to 180,000, etc.
[0050] In some cases, the present invention can control the melt mass flow rate of the first linear low-density polyethylene and the second linear low-density polyethylene to be 1 to 3 g / 10 min, which is beneficial to the fluidity during processing, uniformity of blending and dispersion, and other properties.
[0051] In some cases, the flash point of the processing base oil is above 260°C to reduce volatility during processing and use. For ease of use and storage, the initiator is diisopropylbenzene peroxide (DCP) with a relatively high half-life.
[0052] In the present invention, under the system of the present invention, the silane masterbatch and the catalyst masterbatch can use the same antioxidant, which reduces the complexity of the formula. The present invention preferably makes the first antioxidant and the second antioxidant respectively composed of antioxidant 1010, antioxidant 300, and antioxidant 1024 in a ratio of 1:0.8-1.2:0.8-1.2. Practice shows that adverse factors such as cross-linking side reactions of carbon-carbon bonds in the main chain of the substrate and copper damage during the grafting process can be reduced.
[0053] In the present invention, under the system of the present invention, the silane is vinyl triethoxy silane, which can basically achieve a relatively ideal cross-linking effect in 2-3 days under the system of the present invention, and can also prevent the occurrence of pre-cross-linking or too short downtime in the cable production process.
[0054] In some cases, the catalyst is dibutyltin dilaurate, which has a relatively faster natural crosslinking speed under the system of the present invention.
[0055] In some cases, the flame retardant is magnesium hydroxide and / or zinc borate, and the system of the present invention requires the completion of silane grafting during the cable production process, and the process temperature is relatively high. Therefore, in order to prevent the flame retardant from decomposing and producing too much water, resulting in excessive and rapid hydrolysis of silane, magnesium hydroxide and / or zinc borate with a relatively high decomposition temperature are selected to avoid pre-crosslinking and the formation of defective cables.
[0056] Furthermore, in the present invention, in the formula design of the catalytic masterbatch, compared with the catalytic masterbatch of traditional silane cross-linked polyethylene, an appropriate proportion of SEBS powder is added to the formula, which plays a role in adsorbing liquid catalysts during the production process, making it easy to change the water-drawn strip production method to a hot-cut production method, thereby improving production efficiency and reducing the introduction of moisture, thereby reducing the dehydration and drying environment.
[0057] Furthermore, the preparation method of the above-mentioned silane cross-linked halogen-free flame retardant material comprises:
[0058] (1) Preparation of silane masterbatch
[0059] The first linear low-density polyethylene, the first antioxidant, 90 wt.% to 99.9 wt.% of the first SEBS and the processing base oil are uniformly mixed, and then the flame retardant is added, and after the mixture is uniformly mixed, the mixture is banburyed and extruded into granules, and the obtained particles, the remaining 0.1 wt.% to 10 wt.% of the first SEBS and the silane dissolved with the initiator are mixed to obtain a silane masterbatch without silane grafting;
[0060] (2) Preparation of catalytic masterbatch
[0061] The second linear low-density polyethylene, the second SEBS, the catalyst and the second antioxidant are mixed, kneaded, extruded and granulated to obtain a catalytic masterbatch.
[0062] Furthermore, in some implementation cases, the preparation method of the silane cross-linked halogen-free flame retardant material includes:
[0063] (1) Preparation of silane masterbatch
[0064] The first linear low-density polyethylene, the first antioxidant, 90wt.% to 99.9wt.% of the first SEBS and the processing base oil are sequentially added to a high-speed mixer and stirred evenly, so that the first SEBS fully absorbs the processing base oil, and then the flame retardant is added, mixed evenly, and then banburying and extrusion granulation are performed, and the particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, and a homogenizing silo. When the particles are cooled to no more than 50° C., the particles are added to the high-speed mixer, and the remaining 0.1wt.% to 10wt.% of the first SEBS and the silane dissolved with the initiator are added at the same time. After the silane is added, the mixture is mixed to obtain a silane masterbatch without silane grafting, which can be vacuum packaged;
[0065] (2) Preparation of catalytic masterbatch
[0066] The second linear low-density polyethylene, the second SEBS, the catalyst and the second antioxidant are mixed and kneaded to fully plasticize the materials. Then the material mass is poured into a conical feeder and granulated by twin-screw and single-screw extrusion. The particles are cooled and homogenized through pipelines, cyclone separators, vibrating screens, homogenizing silos, etc. to obtain a catalytic masterbatch, which can be vacuum packaged.
[0067] The silane masterbatch and the catalyst masterbatch are packaged separately according to the proportion to obtain the finished product.
[0068] During cable production, separate the silane masterbatch and the catalyst masterbatch, pour them into a mixer and mix them evenly before use.
[0069] Furthermore, in the above-mentioned preparation process, the process of hot cutting granulation and air cooling can be adopted, which not only directly removes the moisture that may be contained in the raw materials, but also avoids the contact between the particles and water in the processes such as water ring cutting and water strand granulation, omits the process links such as dehydration and drying, saves water resources, reduces the moisture in the particles, and can minimize the pre-cross-linking problem caused by moisture; the use of a homogenizing silo not only improves the consistency of the product, but also reduces the temperature of the pellets to prevent the soft product particles from sticking together.
[0070] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0071] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.
[0072] In the following, LLDPE was purchased from ExxonMobil with the brand name 3518CB; the processing base oil was 150BS; the PE-based silicone masterbatch was purchased from Silike with the brand name 603; the antioxidants were all composed of antioxidant 1010, antioxidant 300, and antioxidant 1024 compounded in a ratio of 1:1:1, and antioxidant 1010, antioxidant 300, and antioxidant 1024 were all purchased from Beijing Jiyi Chemical.
[0073] Example 1
[0074] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof. The silane cross-linked halogen-free flame retardant material comprises a silane masterbatch and a catalytic masterbatch, and the feed mass ratio of the silane masterbatch to the catalytic masterbatch is 19:1;
[0075] In terms of weight, the composition of the silane masterbatch is: 40 parts of SEBS (purchased from China's Taiwan Rubber, brand 6151, molecular weight of about 230,000), 60 parts of LLDPE, silane: 2.0 parts of vinyl triethoxysilane, initiator: 0.04 parts of dicumyl peroxide, lubricant: 2.5 parts of PE-based silicone masterbatch, 25 parts of processing base oil, flame retardant: 72.5 parts of magnesium hydroxide, flame retardant: 2.5 parts of zinc borate, and 1.0 parts of antioxidant;
[0076] In terms of weight, the catalytic masterbatch composition is: 99 parts of LLDPE, 1 part of SEBS (purchased from Taiwan Rubber, brand 6151, molecular weight of about 230,000, purchased from China), 2.0 parts of dibutyltin dilaurate, and 2.0 parts of antioxidant.
[0077] The preparation method comprises:
[0078] (1) The preparation process of silane masterbatch is as follows: LLDPE, lubricant, antioxidant, 99wt.% SEBS and processing base oil are added to a high-speed mixer and stirred evenly, so that SEBS fully absorbs the processing base oil, and then a flame retardant is added to the high-speed mixer and stirred evenly again, and then the materials are added to an internal mixer and internally kneaded to 140° C. to fully plasticize the materials, and then the material mass is poured into a conical feeder, and granulated by twin-screw and single-screw extrusion, and the particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc. When the particles are cooled to no more than 50° C., the particles are added to the high-speed mixer, and the remaining 1wt.% SEBS is added at the same time, and then silane dissolved with an initiator is added while stirring, and after the silane is added, the mixture is stirred for 1 minute, and then vacuum-packed to obtain a silane masterbatch;
[0079] Among them, the temperatures of each section of the twin-screw extruder are: zone 1 125℃, zone 2 130℃, zone 3 135℃, zone 4 140℃, zone 5 145℃, zone 6 150℃, zone 7 155℃, zone 8 155℃, zone 9 155℃, and the die head temperature is 155℃; the temperature of the single-screw extruder is: zone 1 135℃, zone 2 140℃, zone 3 145℃, and the die head temperature is 150℃.
[0080] (2) The preparation process of the catalytic masterbatch is as follows: LLDPE, SEBS, catalyst and antioxidant are uniformly mixed in a high-speed mixer and then put into an internal mixer, and the mixture is internally mixed at 160°C to fully plasticize the material. The material mass is then poured into a conical feeder, and granulated by twin-screw and single-screw extrusion. The particles are cooled and homogenized by passing through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc., and then vacuum packaged to obtain the catalytic masterbatch.
[0081] Among them, the temperatures of each section of the twin-screw extruder are: zone 1 125℃, zone 2 130℃, zone 3 135℃, zone 4 140℃, zone 5 145℃, zone 6 150℃, zone 7 155℃, zone 8 155℃, zone 9 155℃, and the die head temperature is 155℃; the temperature of the single-screw extruder is: zone 1 135℃, zone 2 140℃, zone 3 145℃, and the die head temperature is 150℃.
[0082] The silane masterbatch and the catalyst masterbatch were mixed and stirred at a ratio of 19:1, and then extruded into a sheet in an extruder. The obtained sheet was placed at room temperature for 48 hours, and then cut into samples to obtain test samples.
[0083] Example 2
[0084] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof. The silane cross-linked halogen-free flame retardant material comprises a silane masterbatch and a catalytic masterbatch, and the feed mass ratio of the silane masterbatch to the catalytic masterbatch is 19:1;
[0085] In terms of weight, the composition of the silane masterbatch is: 50 parts of SEBS (purchased from Taiwan Rubber, brand 6154, molecular weight of about 160,000) , 50 parts of LLDPE, silane: 4.0 parts of vinyl triethoxysilane, initiator: 0.17 parts of dicumyl peroxide, lubricant: 2 parts of PE-based silicone masterbatch, 30 parts of processing base oil, flame retardant: 100 parts of magnesium hydroxide, and 3.5 parts of antioxidant;
[0086] The composition of the catalytic masterbatch is as follows: 99 parts of LLDPE, 1 part of SEBS (purchased from Taiwan Rubber, brand 6154, molecular weight about 160,000, purchased from China), 1.5 parts of dibutyltin dilaurate, and 2.0 parts of antioxidant.
[0087] The preparation method comprises:
[0088] (1) The preparation process of silane masterbatch is as follows: LLDPE, lubricant, antioxidant, 99wt.% SEBS and processing base oil are added to a high-speed mixer and stirred evenly to allow SEBS to fully absorb the processing base oil; then a flame retardant is added to the high-speed mixer and stirred evenly again; then the materials are added to an internal mixer and internally kneaded to 150° C. to fully plasticize the materials; then the material mass is poured into a conical feeder and granulated by twin-screw and single-screw extrusion; the particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc.; when the particles are cooled to no more than 50° C., the particles are added to the high-speed mixer, and the remaining 1wt.% SEBS is added at the same time; then silane dissolved with an initiator is added while stirring; after the silane is added, the mixture is stirred for 1 minute; then vacuum-packed to obtain a silane masterbatch;
[0089] Among them, the temperatures of each section of the twin-screw extruder are: zone 1 125℃, zone 2 130℃, zone 3 135℃, zone 4 140℃, zone 5 145℃, zone 6 150℃, zone 7 155℃, zone 8 155℃, zone 9 155℃, and the die head temperature is 155℃; the temperature of the single-screw extruder is: zone 1 135℃, zone 2 140℃, zone 3 145℃, and the die head temperature is 150℃.
[0090] (2) The preparation process of the catalytic masterbatch is as follows: LLDPE, SEBS, catalyst and antioxidant are mixed evenly in a high-speed mixer and then put into an internal mixer and mixed at 150°C to fully plasticize the material. The material mass is then poured into a conical feeder and granulated by twin-screw and single-screw extrusion. The particles are cooled and homogenized by passing through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc., and then vacuum packaged to obtain the catalytic masterbatch.
[0091] Among them, the temperatures of each section of the twin-screw extruder are: zone 1 125℃, zone 2 130℃, zone 3 135℃, zone 4 140℃, zone 5 145℃, zone 6 150℃, zone 7 155℃, zone 8 155℃, zone 9 155℃, and the die head temperature is 155℃; the temperature of the single-screw extruder is: zone 1 135℃, zone 2 140℃, zone 3 145℃, and the die head temperature is 150℃.
[0092] The silane masterbatch and the catalyst masterbatch were mixed and stirred at a ratio of 19:1, and then extruded into a sheet in an extruder. The obtained sheet was placed at room temperature for 48 hours, and then cut into samples to obtain test samples.
[0093] Example 3
[0094] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof. The silane cross-linked halogen-free flame retardant material comprises a silane masterbatch and a catalytic masterbatch, and the feed mass ratio of the silane masterbatch to the catalytic masterbatch is 19:1;
[0095] In terms of weight, the composition of the silane masterbatch is: 60 parts of SEBS (purchased from China's Taiwan Rubber, brand 6150, molecular weight of about 80,000), 40 parts of LLDPE, silane: 6.0 parts of vinyl triethoxysilane, initiator: 0.3 parts of dicumyl peroxide, lubricant: 1.5 parts of PE-based silicone masterbatch, 35 parts of processing base oil, flame retardant: 125 parts of magnesium hydroxide, and 6.0 parts of antioxidant;
[0096] The composition of the catalytic masterbatch is as follows, by weight: 99 parts of LLDPE, 1 part of SEBS (purchased from Taiwan Rubber, brand 6150, molecular weight of about 80,000, purchased from China), 1.0 part of dibutyltin dilaurate, and 2.0 parts of antioxidant.
[0097] The preparation method comprises:
[0098] (1) The preparation process of silane masterbatch is as follows: LLDPE, lubricant, antioxidant, 99wt.% SEBS and processing base oil are added to a high-speed mixer and stirred evenly, so that SEBS fully absorbs the processing base oil, and then a flame retardant is added to the high-speed mixer and stirred evenly again, and then the materials are added to an internal mixer and internally kneaded to 160° C. to fully plasticize the materials, and then the material mass is poured into a conical feeder, and granulated by twin-screw and single-screw extrusion, and the particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc. When the particles are cooled to no more than 50° C., the particles are added to the high-speed mixer, and the remaining 1wt.% SEBS is added at the same time, and then silane dissolved with an initiator is added while stirring, and after the silane is added, it is stirred for 1 minute, and then vacuum-packed to obtain a silane masterbatch;
[0099] Among them, the temperatures of each section of the twin-screw extruder are: zone 1 125℃, zone 2 130℃, zone 3 135℃, zone 4 140℃, zone 5 145℃, zone 6 150℃, zone 7 155℃, zone 8 155℃, zone 9 155℃, and the die head temperature is 155℃; the temperature of the single-screw extruder is: zone 1 135℃, zone 2 140℃, zone 3 145℃, and the die head temperature is 150℃.
[0100] (2) The preparation process of the catalytic masterbatch is as follows: LLDPE, SEBS, catalyst and antioxidant are mixed evenly in a high-speed mixer and then put into an internal mixer and internally kneaded to 140°C to fully plasticize the material. The material mass is then poured into a conical feeder and granulated by twin-screw and single-screw extrusion. The particles are cooled and homogenized by passing through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc., and then vacuum packaged to obtain the catalytic masterbatch.
[0101] Among them, the temperatures of each section of the twin-screw extruder are: zone 1 125℃, zone 2 130℃, zone 3 135℃, zone 4 140℃, zone 5 145℃, zone 6 150℃, zone 7 155℃, zone 8 155℃, zone 9 155℃, and the die head temperature is 155℃; the temperature of the single-screw extruder is: zone 1 135℃, zone 2 140℃, zone 3 145℃, and the die head temperature is 150℃.
[0102] The silane masterbatch and the catalyst masterbatch were mixed and stirred at a ratio of 19:1, and then extruded into a sheet in an extruder. The obtained sheet was placed at room temperature for 48 hours, and then cut into samples to obtain test samples.
[0103] Example 4
[0104] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof, which is basically the same as Example 1, except that: in the preparation of the silane masterbatch, 98 wt.% of SEBS is added before mixing, and the remaining 2.0 wt.% of SEBS is mixed with silane containing an initiator.
[0105] Comparative Example 1
[0106] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof, which is basically the same as Example 1, with the only difference being that the SEBS with a relative molecular weight of about 400,000 (purchased from TSRC in China, brand 6159) is used in the silane masterbatch and the catalyst masterbatch.
[0107] Comparative Example 2
[0108] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof, which is basically the same as Example 1, except that the silane used is vinyltrimethoxysilane.
[0109] Comparative Example 3
[0110] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof, which is basically the same as Example 1, except that SEBS is not added to the catalyst masterbatch.
[0111] Comparative Example 4
[0112] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof, which is basically the same as Example 1, except that in the preparation process of the silane masterbatch, the SEBS is added all at once before the banburying.
[0113] Comparative Example 5
[0114] This example provides a silane cross-linked halogen-free flame retardant material and a preparation method thereof, which is basically the same as Example 1, with the only difference being that in the preparation process of the silane masterbatch, before banburying, SEBS is added all at once, and after granulation, it is prepared according to a method similar to the one-step silane cross-linked polyethylene, specifically: the shaking tank is sealed and the water in the water tank is heated so that the hot water maintains heating of the tank body, and after the tank body reaches the set temperature, the prepared particles are added, and then vacuum is drawn, silane is inhaled, nitrogen is inhaled, and rotation and stirring are maintained for 70 minutes to obtain the silane masterbatch.
[0115] Performance Testing
[0116] The test samples obtained from the above Examples 1-4 and Comparative Examples 1-5 were subjected to the following performance tests, and the specific results are shown in Tables 1 and 2.
[0117] The hardness is tested in accordance with the standard GB / T 2411, and the sample thickness is about 6.0 mm.
[0118] The tensile strength and elongation at break tests were carried out in accordance with the provisions of standard GB / T 1040.3, with a sample thickness of approximately 1.0 mm and a test speed of 250 mm / min.
[0119] The thermal elongation performance was tested in accordance with the provisions of standard GB / T 5470, with a test temperature of approximately 200°C, a test time of 15 min, a test load of 0.2 MPa, and a sample thickness of approximately 1.0 mm.
[0120] The volume resistivity is carried out in accordance with the provisions of standard GB / T 31838.2, and the sample thickness is about 1.0 mm.
[0121] Table 1
[0122]
[0123]
[0124] Table 2
[0125]
[0126] Note 1: The above performance is the test result after being placed at room temperature for 48 hours.
[0127] Note 2: Basis for calculating unit energy consumption: The power of the high-speed mixer in the embodiments and comparative examples is 50kW, the stirring time of each unit is 1 minute, the processing capacity is 120kg, and the energy consumption for producing 1 ton of product is 50×10÷60÷1.2≈6.9kW. In comparative example 5, according to the process of one-step silane cross-linked polyethylene, the equipment heating power is 48kW, the motor and inverter power are both 7.5kW, and the heating time for producing one unit (one unit of about 1.2 tons of output) is about 120 minutes (rotation stirring time is about 70 minutes, vacuuming time is about 10 minutes, and raw material drying is about 40 minutes), and the unit energy consumption is (48×2+70×(7.5+7.5)÷60)÷1.2≈94.6kW (vacuuming energy consumption is not calculated).
[0128] Note 3: Production efficiency, in the embodiments and comparative examples 1-4, the stirring time of each unit of the high-speed mixer is 1 minute, and the processing capacity of each unit is 120 kg. As long as the front-end output can keep up or several production lines share one high-speed mixer, 60 units can be produced per hour, that is, 7.2 tons. In the one-step silane cross-linked polyethylene process in comparative example 5, the output of each unit is about 1 ton, and the time per unit is about 70 minutes (only the rotation stirring time is calculated), so the production capacity per unit time is about 1.2×60÷70≈1 ton. If the whole process time is 120 minutes, the production capacity is only 0.6 tons.
[0129] Note 4: The greater the thermal elongation, the smaller the degree of cross-linking of the material, the greater the thermal elongation or the material is pulled apart, the smaller the strength is generally, the greater the elongation is generally, and the performance is relatively worse;
[0130] The longer the downtime is, the more conducive it is to processing during production, and it can provide enough time for operators to prepare. But it also means that the cross-linkability of the material is poorer, so a reasonable downtime is more important.
[0131] Note 5: Cross-linking energy consumption. The power of the steamer varies. The present invention is calculated based on a steamer power of 50 kW. The steam cross-linking time is generally 4-6 hours. The present invention is calculated based on 5 hours. The energy consumption of a single batch is 50×5=250 kW.
[0132] As can be seen from Table 1-2, the samples prepared according to the formula and process of the present invention can be naturally cross-linked stably and quickly, and the tensile strength, elongation, electrical properties, etc. after cross-linking are good, and at the same time, they have relatively low hardness and good flexibility. By adopting the process of the present invention, the energy consumption of the silane adsorption process is greatly reduced, with a reduction of more than 90%, and the production efficiency is increased by about 6 times, and the effect of reducing consumption and increasing efficiency is very significant. Natural cross-linking does not consume energy and water at all, and does not require related equipment investment.
[0133] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0134] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A method for preparing a silane cross-linked halogen-free flame retardant material, characterized in that: The preparation method comprises: (1) Preparation of silane masterbatch The first linear low-density polyethylene, the first antioxidant, 90 wt.% to 99.9 wt.% of the first SEBS and the processing base oil are uniformly mixed, and then the flame retardant is added, and after the mixture is uniformly mixed, the mixture is banburyed and extruded into granules, and the obtained particles, the remaining 0.1 wt.% to 10 wt.% of the first SEBS and the silane dissolved with the initiator are mixed to obtain a silane masterbatch without silane grafting; Wherein, in parts by weight, the silane masterbatch comprises 40 to 60 parts of the first SEBS, 40 to 60 parts of the first linear low-density polyethylene, 2.0 to 6.0 parts of silane, 0.04 to 0.3 parts of initiator, 25 to 35 parts of processing base oil, 75 to 125 parts of flame retardant, and 1.0 to 6.0 parts of the first antioxidant; the silane is vinyl triethoxysilane; (2) Preparation of catalytic masterbatch The second linear low-density polyethylene, the second SEBS, the catalyst and the second antioxidant are mixed, kneaded, extruded and granulated to obtain a catalytic masterbatch; Wherein, in the catalyst masterbatch, by weight, the second linear low-density polyethylene is 90-99.5 parts, the second SEBS is 0.5-10 parts, the catalyst is 0.5-3 parts, and the second antioxidant is 0.5-4 parts; The molecular weights of the first SEBS and the second SEBS are respectively 80,000 to 230,000.
2. The method for preparing a silane cross-linked halogen-free flame retardant material according to claim 1, characterized in that: During the preparation of the silane masterbatch, 95 wt.% to 99.9 wt.% of the first SEBS is added before the banburying.
3. The method for preparing a silane cross-linked halogen-free flame retardant material according to claim 1, characterized in that: During the preparation of the silane masterbatch, the temperature of the obtained particles is controlled to be less than or equal to 50° C. before mixing with other materials.
4. The method for preparing a silane cross-linked halogen-free flame retardant material according to claim 1, characterized in that: In the preparation process of the silane masterbatch or the catalytic masterbatch, the temperature of the banburying is 140-160°C; and / or, in the preparation process of the silane masterbatch or the catalytic masterbatch, the extrusion granulation is carried out by a twin-screw extruder and a single-screw extruder in sequence, and the temperatures of the various sections of the twin-screw extruder are: zone 1 120-130°C, zone 2 125-135°C, zone 3 130-140°C, zone 4 140-150°C, zone 5 150-160°C, zone 6 150-170°C, zone 7 150-180°C, zone 8 150-190°C, zone 9 150-190°C, zone 10 150-180°C, zone 11 150-1150°C, zone 12 150-130°C, zone 13 150-1 The temperatures of the first zone and the second zone are 135-145°C, 140-150°C, 145-155°C, 150-160°C, 150-160°C, and 150-160°C, respectively. The temperature of each section of the single-screw extruder is as follows: 130-140°C in the first zone, 135-145°C in the second zone, 140-150°C in the third zone, and 145-155°C, respectively.
5. The method for preparing a silane cross-linked halogen-free flame retardant material according to claim 1, characterized in that: In the silane masterbatch, the total amount of the first SEBS and the first linear low-density polyethylene is 100 parts; and / or, in the catalytic masterbatch, the total amount of the second linear low-density polyethylene and the second SEBS is 100 parts.
6. The method for preparing a silane cross-linked halogen-free flame retardant material according to claim 1, characterized in that: The silane masterbatch further comprises a lubricant, and in the silane masterbatch, the lubricant accounts for 1.5 to 2.5 parts by weight; the lubricant is a PE-based silicone masterbatch, and the silicone content is 40 wt.% to 60 wt.%.
7. The method for preparing a silane cross-linked halogen-free flame retardant material according to claim 1, characterized in that: In the silane masterbatch or the catalytic masterbatch, the first antioxidant and the second antioxidant are the same and are both composed of antioxidant 1010, antioxidant 300, and antioxidant 1024 in a ratio of 1:0.8-1.2:0.8-1.
2.
8. The method for preparing a silane cross-linked halogen-free flame retardant material according to claim 1, characterized in that: Under the conditions of a temperature of 190°C and a load of 2.16 kg, the melt mass flow rates of the first linear low-density polyethylene and the second linear low-density polyethylene are respectively 1-3 g / 10 min; and / or the flash point of the processing base oil is above 260°C; and / or the initiator is diisopropylbenzene peroxide; and / or the flame retardant is magnesium hydroxide and / or zinc borate; and / or the catalyst is dibutyltin dilaurate; and / or the mass ratio of the silane masterbatch to the catalytic masterbatch is 90-99:10-1.
9. A silane cross-linked halogen-free flame retardant material prepared by the method for preparing a silane cross-linked halogen-free flame retardant material according to any one of claims 1 to 8.
10. Use of the silane cross-linked halogen-free flame retardant material according to claim 9 in preparing insulating materials for electronic wires, new energy vehicle charging pile cables and in-vehicle connecting cables.